Musical Language as Humanities Discourse: Ecological Criticism in Navicula’s Songs - Sofyaningrun, Rosita (Fakultas Ilmu Sosial dan Politik, Universitas Negeri Surabaya, 2025)
Abstract Song lyrics play an important role in conveying social and environmental messages to the public. This study analyzes the lyrics of Navicula’s songs as a reflection and influence on social discourse regarding the environmental crisis. Using a critical discourse analysis method, this research examines how Navicula's lyrics depict ecological issues such as deforestation, wildlife exploitation, urban pollution, and environmental degradation. The findings reveal that Navicula's lyrics not only represent the reality of the environmental crisis but also serve as an advocacy tool that fosters collective awareness and promotes social action. Through the use of straightforward, metaphorical, and ironic language, Navicula’s songs effectively critique unsustainable environmental policies and challenge the concept of green capitalism. These findings contribute to the advancement of knowledge in the field of education, particularly in utilizing music as a critical learning medium for environmental awareness. By understanding how song lyrics can build ecological consciousness, this study provides new insights for educators in developing art-based teaching methods to enhance students' understanding of environmental issues. Keywords: Song lyrics, Navicula, Environmental Crisis, Social Discourse, Ecological Awareness Abstrak Lirik lagu memiliki peran penting dalam menyampaikan pesan sosial dan lingkungan kepada masyarakat. Penelitian ini menganalisis lirik lagu-lagu Navicula sebagai refleksi dan pengaruh terhadap wacana sosial tentang krisis lingkungan. Dengan menggunakan metode analisis wacana kritis, penelitian ini mengkaji bagaimana lirik lagu-lagu Navicula menggambarkan isu-isu ekologis seperti deforestasi, eksploitasi satwa liar, polusi urban, dan pencemaran lingkungan. Hasil penelitian menunjukkan bahwa lirik lagu Navicula tidak hanya merepresentasikan realitas krisis lingkungan tetapi juga berfungsi sebagai alat advokasi yang mampu membentuk kesadaran kolektif dan mendorong aksi sosial. Melalui penggunaan bahasa yang lugas, metaforis, dan penuh ironi, lagu-lagu Navicula berhasil mengkritisi kebijakan lingkungan yang tidak berkelanjutan serta menantang konsep kapitalisme hijau. Temuan ini berkontribusi terhadap perkembangan ilmu pengetahuan di bidang pendidikan, khususnya dalam pemanfaatan musik sebagai media pembelajaran kritis tentang lingkungan. Dengan memahami bagaimana lirik lagu dapat membangun kesadaran ekologi, penelitian ini memberikan wawasan baru bagi pendidik dalam mengembangkan metode pengajaran berbasis seni untuk meningkatkan pemahaman siswa tentang isu lingkungan. Kata Kunci: Lirik lagu, Navicula, Krisis Lingkungan, Wacana Sosial, Kesadaran Ekologi